PERFORMANCE INVESTIGATION OF SINGLE-PHASE TRANSFORMERLESS PV INVERTER CONNECTED TO LOW VOLTAGE NETWORK (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2024)
Due to their high efficiency and reduced size and weight compared to transformer-based inverters, transformerless single-phase inverters are the most widely used in photovoltaic systems connected to the low-voltage grid. Unfortunately, the absence of galvanic isolation leads to ground faults caused by capacitive leakage current flow and deterioration of the inverter's insulation resistance on the dc side. This paper examines the performance of the three transformerless single-phase inverters of the first grid-connected photovoltaic system in Algeria under adverse weather conditions, such as rain, as there is no galvanic isolation between the dc and ac side of the inverter, making operation of the photovoltaic system more difficult. The flow of capacitive leakage current from the earth to the inverter output is one of the two phenomena, resulting in protection devices being triggered involuntarily. The second phenomenon is system shutdown due to a decrease in the inverter's insulation resistance at the input. The VDE 126-1-1 standard integrated into the inverter, which defines the safety requirements for grid-connected photovoltaic systems, is used in this article to manage and analyze both phenomena.
Keywords: Grid-connected photovoltaic (PV) system; Transformerless PV inverter; Galvanic isolation; Leakage current; Insulation resistance